CRIMINAL SANCTIONS: IMPLICATIONS FOR TRAFFIC VIOLATIONS - Setiawati, Sri; Hartati, Sri (Jurnal Hukum Khaira Ummah, 2023)
It is known that traffic rules are made to protect the interests of road users, even though in reality there are still many road users who violate traffic rules. The government and DPR made regulations contained in Law No. 22 of 2009. This law is considered less than optimal because ordinary people often think that the police decide the amount of the violation fund which is called "deposit money" for criminal fines for past violations. cross. The purpose of this research is to review the application of criminal fines for traffic regulations based on Law No. 22 of 2009. This research is qualitative research using data collection methods, data presentation methods, and data analysis methods. The theory used in this research is Legal Theory which is detailed in depth. The results of the research show that the implementation of criminal fines for violators of traffic regulations is broken down into 4 sub-chapters, namely (1) Violations of Traffic Regulations, (2) Various Traffic Violations According to No. 22 of 2009, (3) Criminal Sanctions of Fines, and (4) Judge's Decision and Implementation of Criminal Sanctions of Fines to people who violate Traffic Regulations; and Obstacles that often occur in the implementation of criminal compensation penalties for violating traffic regulations and efforts to resolve them.Keywords : police, fines, traffic regulations